A study on the awareness, utilisation and perception of the government assistance schemes by the small and medium sized firms in the textile and garment industry. - Chua, Angela Poh Neo. (2008)
A survey was conducted among the member firms of the Textile and Garment Manufactures Association of Singapore and its purpose was threefold.